2009
DOI: 10.1152/ajpheart.00068.2009
|View full text |Cite
|
Sign up to set email alerts
|

Doxorubicin induces senescence or apoptosis in rat neonatal cardiomyocytes by regulating the expression levels of the telomere binding factors 1 and 2

Abstract: The mechanism by which different doses of doxorubicin may induce different stress-response cellular programs is not well understood. A recent study showed that the level of telomere dysfunction may induce senescence or apoptosis. We investigated the pathways to both apoptosis and senescence in neonatal rat cardiomyocytes and in H9c2 cells exposed to a single pulsed incubation with low or high doses of doxorubicin. High-dose doxorubicin strongly reduces TRF2 expression while enhancing TRF1 expression, and it de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
109
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(124 citation statements)
references
References 60 publications
14
109
1
Order By: Relevance
“…The data obtained here demonstrated that doxorubicin induced the expression of the tumor suppressor protein p53. This is in agreement with previous studies reporting that the drug can intercalate DNA, generating reactive oxygen species, leading to a DNA damageresponse mediated by p53 [26,44]. Coincident with these findings, our data provided evidence that doxorubicin was able to promote in lung mucoepidermoid NCI-H292 cells the activation of DNA damage response as suggested by the increase in gH2AX.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The data obtained here demonstrated that doxorubicin induced the expression of the tumor suppressor protein p53. This is in agreement with previous studies reporting that the drug can intercalate DNA, generating reactive oxygen species, leading to a DNA damageresponse mediated by p53 [26,44]. Coincident with these findings, our data provided evidence that doxorubicin was able to promote in lung mucoepidermoid NCI-H292 cells the activation of DNA damage response as suggested by the increase in gH2AX.…”
Section: Discussionsupporting
confidence: 93%
“…For example, doxorubicin, an anthracycline antitumor drug widely used in clinical chemotherapy, induces senescence at low doses and apoptosis at high doses in breast cancer cells and in neonatal rat cardiomyocytes [24,25,26]. Hsp60 over-expression suppressed doxorubicin-induced apoptosis in cardiomyocytes [27], and doxorubicin-induced apoptosis in HeLa cells triggering Hsp60 up-regulation [23].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, DOX-treated hearts exhibited aging-related alterations including the upregulation of SA-b-gal activity and expression of cell cycle inhibitors and proinflammatory cytokines ( Supplementary Fig. S2b-d) [20][21][22] . CCCP-induced Parkin and p62 translocation was also reduced in DOX-treated hearts (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Notwithstanding, the cardiotoxicity of anthracyclines is well documented; the secondary effects are mainly cardiomyopathy and cardiac syncope (5). Epidemiologic studies indicate that 50% of patients exposed to anthracyclines develop cardiac abnormalities after 10 to 20 years of chemotherapy; 40% of patients present with arrhythmia and 5% with heart failure (6).…”
Section: Introductionmentioning
confidence: 99%